The effect of candidate electoral experience on ballot placement in list proportional representation systems. Issue 4 (7th June 2021) - Put, Gert-Jan; Muyters, Gertjan; Maddens, Bart
Abstract: This article investigates how candidate experience in previous elections, measured by the number of prior candidacies, affects ballot placement in list PR systems. The central argument is that selectorates find experienced candidates attractive because of proven loyalty and higher voter recognition. Moreover, prior candidacies strengthen candidates' familiarity with intra-party selection processes. Returning candidates, however, also risk becoming victims of a seniority trap: after not succeeding to access realistic positions after a number of elections, additional candidacies become harmful as selectorates lose interest. Using data on 18, 393 candidacies by 9, 905 candidates of parties in Flanders (Belgium) (1987–2019), a set of logit and Cox models test the hypothesised curvilinear effect of prior candidacies on access to realistic positions. Both approaches lead to similar outcomes, confirming that experience positively affects ballot placement but with decreasing marginal utility. These findings have important implications for career strategies and contribute to knowledge on nomination processes and candidate turnover.